Color Modification of Andong Bamboo (Gigantochloa pseudoarundinacea) through Oil Heat Treatment: Aesthetic Enhancement and Consumer Preferences - Hafizh Awandi; Indra Gumay Febryano; Afif Bintoro; Intan Fajar Suri; Wahyu Hidayat (Green Insight Solutions, 2025)
Bamboo is a sustainable alternative to wood and is classified as a non-timber forest product. The primary raw material for this research is andong bamboo (Gigantochloa pseudoarundinacea). which exhibits vivid physical coloration that may reduce its aesthetic appeal. Additionally, it is susceptible to fungal and insect infestations. Heat treatment has been identified as an effective method for modifying the color properties of bamboo, with oil heat treatment offering potential advantages. This study investigated the impact of oil heat treatment on the color properties of andong bamboo and evaluates consumer preferences regarding its modified appearance. Andong bamboo specimens were subjected to oil bath at temperatures of 180°C, 200°C, 220°C, and 240°C for three hours. Colorimetric analysis was conducted using the CIE-Lab system, measuring parameters such as lightness (L*), red-green chromaticity (a*), yellow-blue chromaticity (b*), and overall color change (ΔE*). The results indicate a significant reduction in L* values with increasing treatment temperature, leading to a darker appearance. Similarly, a* and b* values decreased, indicating a shift in chromatic characteristics. A value of ΔE* above 12 suggests a total color change. Consumer preference analysis revealed that respondents favored andong bamboo heat-treated at 180°C and 200°C, perceiving these treatments as producing a more exotic and visually appealing. These findings suggest that oil heat treatment not only enhances the aesthetic value of andong bamboo but also increases its potential for high-value applications in furniture and interior design.